The legacy of ad hoc tribunals in international criminal law : assessing the ICTY's and the ICTR's most significant legal accomplishments / edited by Milena Sterio, Michael P. Scharf. - Sterio, Milena; Scharf, Michael P., 1963- (Cambridge University Press, 2019)
In the post-Nuremberg era two of the most important developments in international criminal law are the International Criminal Tribunal for Yugoslavia (ICTY) and the International Criminal Tribunal for Rwanda (ICTR). Created through UN Security Council resolutions, with specific mandates to prosecute those responsible for serious violations of international humanitarian law, the ICTY and the ICTR played crucial roles in the development of international criminal law. Through a series of chapters written by leading authorities in the field, The Legacy of Ad Hoc Tribunals in International Criminal Law addresses the history of the ICTY and the ICTR, and the important aspects of the tribunals' accomplishments. From examining the groundwork laid by the ICTY and the ICTR for greater international attention to crimes against humanity to the establishment of the International Criminal Courts, this volume provides a comprehensive overview of the impact and lasting roles of these tribunals.